Fulminant wound infection with Clostridium perfringens and Bacillus cereus in a healthy five year old boy - Thomas Koelbl; Sara Bernhard; Barbara Egger; Claudia Meuli-Simmen; Thuan Ly (Elsevier, 2018)
Trauma related soft tissue infections with Clostridium perfringens and Bacillus cereus in children are rare. We report a case of a healthy five-year old boy with a posttraumatic fulminant localized necrotisizing facial soft tissue infection.A five-year old healthy boy was admitted after a sledging accident. He presented with a laceration of the right cheek. Within 12 h after rinsing and primarily closure under analgosedation he developed localized severe pain and fever. Immediate wound revision under general anesthesia revealed necrotic subcutaneous tissue with an abscess cavity. After surgical debridement the wound was initially left open. An empiric antibiotic therapy with amoxicillin/clavulanate was initiated. A facial bone fracture was excluded by computed tomography. C. perfringens., B. cereus, B. licheniformis and B. pumilus were recovered. A correct intravenous combination therapy was initiated followed by secondary wound closure. The local situation and general condition of the boy improved markedly and no further intervention was necessary. Keywords: Infection, Children, Clostridium perfringens, Bacillus cereus, Trauma